Pengaruh Capital Intensity, Inventory Intensity, dan Leverage terhadap Tax Avoidance pada Perusahaan Manufaktur Sektor Aneka Industri dan Sektor Industri Dasar dan Kimia yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2017-2019 - Dwi Salsabila; Untung Wahyudi; Dwi Anggarani (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
This study aims to examine the influence of capital intensity, inventory intensity, and leverage on tax avoidance both partially and simultaneously. The objects used in this research are manufacturing companies in the various industrial sectors and basic industrial and chemical sectors, with research years spanning 3 periods in 2017 – 2019. Manufacturing companies in the various industrial sector and basic industrial and chemical sector until 2019 had a population of 124 companies. Sampling in the research used a purposive sampling technique to obtain 41 companies used in the research sample. The data analysis method used is multiple linear regression analysis using IBM SPSS version 25 software. The research results show that partially the three variables, namely capital intensity, inventory intensity, and leverage, have a positive and significant effect on tax avoidance. Likewise, the result of research simultaneously show that the three independent variables have a positive and significant effect on tax avoidance.